2023
DOI: 10.3390/math11051244
|View full text |Cite
|
Sign up to set email alerts
|

On Horadam Sequences with Dense Orbits and Pseudo-Random Number Generators

Abstract: Horadam sequence is a general recurrence of second order in the complex plane, depending on four complex parameters (two initial values and two recurrence coefficients). These sequences have been investigated over more than 60 years, but new properties and applications are still being discovered. Small parameter variations may dramatically impact the sequence orbits, generating numerous patterns: periodic, convergent, divergent, or dense within one dimensional curves. Here we explore Horadam sequences whose or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…is satisfied, then the value X = W β+W will be accepted. Regarding the choice of θ, in [49], it was concluded that taking θ = 1/(α + β) is the best option to maximise the conditional probability of satisfying the test in Equation (9) given that the algorithm is accepted. This value for θ causes a drawback: it must be ensured that α < β.…”
Section: Cheng's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…is satisfied, then the value X = W β+W will be accepted. Regarding the choice of θ, in [49], it was concluded that taking θ = 1/(α + β) is the best option to maximise the conditional probability of satisfying the test in Equation (9) given that the algorithm is accepted. This value for θ causes a drawback: it must be ensured that α < β.…”
Section: Cheng's Methodsmentioning
confidence: 99%
“…It is at this point that we will take a closer look at some of the most important concepts related to random and pseudo-random sequences and the tests that must be carried out to check the quality of the sequences. In general, it is possible to speak of true random numbers and pseudo-random numbers (see, for example, [6][7][8][9][10][11] among others). The former are based on physical sources and do not need an initial input to be generated.…”
Section: Introductionmentioning
confidence: 99%